A Novel Procedure for Quick Design of Off-Grid PV Water Pumping Systems for Irrigation - Klimenta, Dardan; Lekic, Julijana; Arsic, Sanela; Tasic, Dragan; Krstic, Nikola; Radosavljevic, Dragana (Elektronika ir Elektrotechnika, 2021)
It is known that meteorological variables from meteorological online services can be used for the design of photovoltaic (PV) water pumping systems for irrigation. The software LORENTZ COMPASS in such a manner uses as inputs solar irradiation, precipitation, and ambient temperature collected by the NASA Langley Research Centre over a period of more than 20 years. This paper proposes a novel procedure that uses the sunshine duration, precipitation, and ambient temperature as inputs. These inputs were collected by Weather Online UK during a period of 25 years. The effects of different data collection periods and data availabilities on the design of the PV water pumping system are also analysed and discussed. Along with the meteorological data, the proposed procedure uses as inputs datasheets from manufacturers of pumping systems and PV modules. The procedure is based on the Sivkov model that correlates the global horizontal irradiation with the sunshine duration and the elevation angle of the Sun. A case study, i.e., an existing PV water pumping system designed using LORENTZ COMPASS is used as reference for purposes of comparison and validation of the procedure. The results of the comparison showed a high level of accuracy, and a number of interesting conclusions are drawn from them.